FORMALISTIC READING ON TENSION AND THEME IN TWO POEMS: CHARLES TOMLINSONÃ¢â¬â¢S WINTER ENCOUNTERS AND ROBERT FROSTÃ¢â¬â¢S THE VALLEYÃ¢â¬â¢S SINGING DAY - Yulianto, Henrikus Joko (Language Circle: Journal of Language and Literature, 2009)
A poetic text has its own aesthetic values through its form and language. This statement was proposed by a movement called Formalism and later was known as New Criticism. The movement assumed that the aesthetic qualities of a poem are revealed in its poetic devices such as imagery, meter, symbol, and the like. New Critics assumed that an interpretation of a poetic text in regard to the author or the historical background will bring about what they called as the Intentional and Affective Fallacies. Otherwise, a poetic text will convey a certain meaning through its own devices. New Critics assume that language devices of poetic works embody some paradoxes or discordant and contrary qualities. Not only focusing on ambiguity, irony, and paradox, the New Critics also find out a tension or a reconciliation of the conflicts through a close reading on the poetic devices of the works themselves. Meanwhile, a poetic work will also suggest a certain central idea or theme. In this case, a close reading of the two poems is meant to find similarities and differences of the tension and theme in both poems. ÃÂ  Key Words: ÃÂ  Formalism, New Criticism, Tension, Ambiguity, Irony, Paradox, the Intentional and Affective Fallacies